KARAWITAN TARI TOPENG SEKARTAJI TUNGGAL - Rini Rahayu (Keteg : Jurnal Pengetahuan, Pemikiran dan Kajian Tentang Bunyi, 2018)
AbstractTopeng Sekartaji Tunggal is dance which is inspired from the inner turmoil of the Dewi Sekartaji, a beloved daughter of protagonist Panji Asmarabangun commonly contained in narratives of Serat Panji. This research aims to know karawitan dance musical idea "Topeng Sekartaji Tunggal" corresponding to shape and work on choreography and describe the creative process when it embodies the idea of a musical idea into a tangible form gamelan musicians dance "Topeng Sekartaji Tunggal". This research uses the steps that consists of three stages, namely 1) Design the idea of Musicians: the Sekartaji mask dance with) the idea of the contents; b) work on the idea; and c) preparation of the implementation. 2) Topeng Sekartaji Tunggal dance Musicians composition process: a) Determine Material Repertoire; and b) process of the exercise. 3) Results of the work: a) results of Product; b) refinements to the Follow-up. The research results obtained are know karawitan idea design, process, and outcomes karawitan Topeng Sekartaji Tunggal dance.Â Keywords: design idea, kekaryaan, karawitan, Topeng Sekartaji Tunggal.Â AbstrakTopeng Sekartaji Tunggal merupakan tarian yang terinspirasi dari gejolak batin Dewi Sekartaji, seorang tokoh protagonis putri kekasih Panji Asmarabangun yang umum termuat dalam kisah-kisah â€œSerat Panjiâ€. Penelitian ini bertujuan untuk Mengetahui ide gagasan musikal karawitan tari â€œTopeng Sekartaji Tunggalâ€ yang sesuai dengan bentuk dan garap koreografi tariannya dan mendeskripsikan proses kreatif ketika mewujudkan ide gagasan musikal menjadi bentuk nyata gending karawitan tari â€œTopeng Sekartaji Tunggalâ€. Penelitian ini menggunakan langkah-langkah yang terdiri dari tiga tahap, yaitu 1) Rancang Gagasan Karawitan Tari Topeng Sekartaji Tunggal: a) Gagasan Isi; b) Gagasan Garap; dan c) Persiapan Penggarapan. 2) Proses Kekaryaan Karawitan Tari Topeng Sekartaji Tunggal: a) Menentukan Materi Gending; dan b) Proses Latihan. 3) Hasil Kekaryaan: a) Capaian Hasil Kekaryaan; b) Tindak Lanjut Penyempurnaan. Hasil penelitian yang diperoleh adalah mengetahui rancang gagasan karawitan, proses kekaryaan karawitan, dan hasil kekaryaan tari Topeng Sekartaji Tunggal.Â Kata kunci: rancang gagasan, kekaryaan, karawitan, Topeng Sekartaji Tunggal.